PKM DIGITAL MARKETING: TRANSFORMATION OF MALSA CHOCOLATE BUSINESS IN MARA FOOD INDUSTRY COMPLEX, MALAYSIA - Supriadi, Yudi Nur; Kusmana, Agus; Ali, Syarif; Hadi, Prasetyo; Manggabarani, Alfatih; Astuti, Amillia; Hanafia, Muhammad (International Journal of Engagement and Empowerment (IJE2), 2024)
MSMEs in Malaysia are facing new challenges in market competition, especially in the rapidly growing digital marketing. Fierce competition requires business actors to adopt effective digital marketing strategies to increase competitiveness and business growth. This Community Service Program (PKM) aims to identify the right digital marketing techniques for the Malsa Chocolate business in the MARA Food Industry Complex, Malaysia. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and literature studies from various secondary sources such as books, articles, and journals. The results of PKM activities explained that digital marketing has been developed, its implementation is still limited. Many business actors in PANGAN MARA have not fully utilized their digital marketing strategies optimally, thus impacting their business productivity and competitiveness. Collaborative efforts are needed between business actors and stakeholders to improve understanding and implementation of digital marketing strategies. With structured assistance and optimal use of technology, MSMEs in PANGAN MARA can be more competitive in the digital market. This research provides recommendations for business actors to adopt more effective digital-based marketing strategies to increase business growth and sustainability